Competitive Modulation of Ca(2+) Release-activated Ca(2+) Channel Gating by STIM1 and 2-Aminoethyldiphenyl Borate - Yamashita, Megumi (American Society for Biochemistry and Molecular Biology, 2011)
Activation of Ca(2+) release-activated Ca(2+) channels by depletion of intracellular Ca(2+) stores involves physical interactions between the endoplasmic reticulum Ca(2+) sensor, STIM1, and the channels composed of Orai subunits. Recent studies indicate that the Orai3 subtype, in addition to being store-operated, is also activated in a store-independent manner by 2-aminoethyldiphenyl borate (2-APB), a small molecule with complex pharmacology. However, it is unknown whether the store-dependent and -independent activation modes of Orai3 channels operate independently or whether there is cross-talk between these activation states. Here we report that in addition to causing direct activation, 2-APB also regulates store-operated gating of Orai3 channels, causing potentiation at low doses and inhibition at high doses. Inhibition of store-operated gating by 2-APB was accompanied by the suppression of several modes of Orai3 channel regulation that depend on STIM1, suggesting that high doses of 2-APB interrupt STIM1-Orai3 coupling. Conversely, STIM1-bound Orai3 (and Orai1) channels resisted direct gating by high doses of 2-APB. The rate of direct 2-APB activation of Orai3 channels increased linearly with the degree of STIM1-Orai3 uncoupling, suggesting that 2-APB has to first disengage STIM1 before it can directly gate Orai3 channels. Collectively, our results indicate that the store-dependent and -independent modes of Ca(2+) release-activated Ca(2+) channel activation are mutually exclusive: channels bound to STIM1 resist 2-APB gating, whereas 2-APB antagonizes STIM1 gating.